Analysis of the Influence of Leadership Style, Organizational Communication, and Work Discipline on Employee Performance at the Transportation Agency of Binjai City - Nabillah Ega Mavira; Batubara, Soulthan Saladin; M. Chaerul Rizky (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
discipline have a positive and significant effect on employee performance at the Binjai City Transportation Agency. The research method is causal associative research with the help of the SPSS Version 26 program. This study uses multiple linear regression. The population in this study was 62 respondents. The sample in this study was 62 respondents. Primary data collection used a questionnaire. The results of the study indicate that leadership style partially has a positive and significant effect on employee performance at the Binjai City Transportation Agency. Organizational communication partially has a positive and significant effect on employee performance at the Binjai City Transportation Agency. Work discipline partially has a positive and significant effect on employee performance at the Binjai City Transportation Agency. Leadership style, organizational communication and work discipline simultaneously have a positive and significant effect on employee performance at the Binjai City Transportation Agency.